2012
DOI: 10.1159/000338817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Bifurcation Angle on Clinical Outcomes after Percutaneous Coronary Intervention in Real-World Practice: Results from the COBIS Registry

Abstract: Objectives: Bifurcation angle has emerged as a predictor of outcome after percutaneous coronary intervention (PCI) for bifurcation lesions. We investigated the impact of bifurcation angle on clinical outcomes in patients undergoing bifurcation lesion PCI. Methods: Consecutive patients who received PCI for bifurcation lesions were enrolled from 16 centers in Korea between January 2004 and June 2006. Patients were divided into low-angle and high-angle groups using the median bifurcation angle (50°). We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…However, Chen et al in their study demonstrated that, when utilizing crush stenting techniques for coronary bifurcation lesions, the angle B did not influence clinical outcomes. The result of this study was in disagreement with the report of Dzavik et al In a substudy from the COBIS trial, angle B did not influence long‐term clinical outcome in patients with non‐left main bifurcation lesion undergoing PCI in real‐world clinical practice . In a substudy from the SYNTAX trial, Girasis and colleagues evaluated the bifurcation angle parameters of the left main coronary artery and the impact of BA on clinical outcome .…”
Section: Introductioncontrasting
confidence: 74%
“…However, Chen et al in their study demonstrated that, when utilizing crush stenting techniques for coronary bifurcation lesions, the angle B did not influence clinical outcomes. The result of this study was in disagreement with the report of Dzavik et al In a substudy from the COBIS trial, angle B did not influence long‐term clinical outcome in patients with non‐left main bifurcation lesion undergoing PCI in real‐world clinical practice . In a substudy from the SYNTAX trial, Girasis and colleagues evaluated the bifurcation angle parameters of the left main coronary artery and the impact of BA on clinical outcome .…”
Section: Introductioncontrasting
confidence: 74%
“…The interquartile range of BA was 29° (40°–69°). In accordance with previous reports , the lesions were divided into low angle and high angle groups using the median BA as follows: 600 lesions (587 patients) in the low angle group (≤52°) and 600 lesions (584 patients) in the high angle group (>52°) (Fig. ).…”
Section: Resultsmentioning
confidence: 88%
“…The importance of BA on bifurcation intervention has been recognized, and both periprocedural and long‐term results can be influenced by bifurcation angulations . However, the exact influence of BA on SB occlusion has not been fully elucidated and the results of previous studies have been contradictory . As such, how BA impacts the fate of the SB after main vessel (MV) stenting remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The 2‐stent technique included various techniques such as T‐stenting technique ( n = 12, 19.1% of 2‐stent technique), crush technique ( n = 35, 55.6%), kissing (or V‐) stent technique ( n = 5, 7.9%), culottes technique ( n = 7, 11.1%), and other techniques ( n = 4, 6.3%) (Table ). Bifurcation angle was defined as the angle between the dMB and SB at its origin using the angiographic projection with the widest separation of the two branches . Stent thrombosis (ST) was also assessed based on the definitions of the Academic Research Consortium as definite, probable, or possible ST .…”
Section: Methodsmentioning
confidence: 99%